Synthesis and Crystal Structure of 4-Phenyl-3-(pyridin-4-yl)-1H-1,2,4-triazole-5(4H)-thione - Gao, Wei; Guo, Feng-Peng; Yang, Jing (Asian Journal of Chemistry, 2014)
A triazole derivative i.e., 4-phenyl-3-(pyridin-4-yl)-1H-1,2,4-triazole-5(4H)-thione was synthesized and its structure was studied by X-ray diffraction. The crystals are orthorhombic, space group pbcn with a = 11.337 (2), b = 12.789 (3), c = 17.625 (4) Å, a = 90.00, b = 90, g = 90°, V = 2555.4 (9) Å3, Z = 8, F(000) = 1056, Dc = 1.322 g/cm3, μ = 0.240 cm-1, the final R = 0.0528 and wR = 0.1429. A total of 19773 reflections were collected, of which 2254 were independent (Rint = 0.043).